Reductimetric Determination of Peroxydisulphate with Iron(II) in Phosphoric Acid Medium Using Resorufin as a Redox Indicator - Vijaya Raju, K.; Rambabu, T. (Asian Journal of Chemistry, 2013)
A simple, accurate and direct reductimetric titration method has been developed for the determination of peroxydisulphate or persulphate using iron(II) as reductant in high phosphoric acid medium (9 M), employing resorufin as a redox indicator. The colour transition of the indicator at the end-point (from red to blue-green) is sharp and reversible. Persulphate in the range 15-50 has been determined with an accuracy of ± 0.6 %. The precision of the method has been determined by computing the pooled standard deviation (0.06 mg) and 95 % confidence limits. In this method persulphate is rapidly and quantitatively reduced to sulphate in a two electron reduction step while resorufin is reduced to its corresponding semiquinone in a one electron reduction step by iron(II). The formal redox potentials of the oxidant system [persulphate/ sulphate couple] and those of the reductant system [iron(III)/iron(II) couple] (under the optimum titration conditions) and the transitional potential of the indicator have been measured. Based on these potentials data, the conditions need in the titration have been offered. The interferences due to diverse ions has been studied.